Lung Toxicity Occurring During Enfortumab Vedotin Treatment: From a Priming Case Report to a Retrospective Analysis - Grégoire Desimpel; François Zammit; Sarah Lejeune; Guillaume Grisay; Emmanuel Seront (MDPI AG, 2024)
Background/Objectives: Enfortumab vedotin (EV) is an antibody-drug conjugate (ADC) that combines monomethyl auristatin E (MMAE), a potent cytotoxic agent, with a monoclonal antibody targeting Nectin-4. It has emerged as a promising therapy for metastatic urothelial carcinoma (mUC), either as monotherapy or in combination with pembrolizumab, improving significantly the overall survival of these patients. EV is associated with common adverse events, including skin reactions, glucose imbalance, and peripheral neuropathy, which are usually mild in severity and easily manageable. Methods: Following an initial case of pleuro-pneumopathy occurring in a patient treated with EV, we conducted a retrospective analysis of EV effects on pulmonary imaging. Results: In a cohort of 20 all-comers mUC patients, we identified three cases of potentially EV-related lung toxicity, resulting in a pleuro-pneumopathy rate of 15%. Two of these cases appeared highly symptomatic and required high steroid doses, with a rapid resolution of symptoms and normalization of radiological findings. In one patient, rechallenge of EV was associated with reoccurrence of pneumopathy. We described the clinical and radiological features of these cases, as well as their evolution after EV discontinuation and rechallenge. Conclusions: This case series underscores the importance of close pulmonary monitoring during EV treatment.